A Cadaver Feasibility Study of Extradural Contralateral C7 Ventral Root Transfer Technique for Treating Upper Extremity Paralysis. Issue 17 (1st September 2022) - Chang, Jie; Wang, Binyu; Yu, Lipeng; Wang, Tong; Sui, Tao; Zhu, Yi; Cao, Xiaojian; Yang, Kaixiang
Abstract : Study Design: A total of 6 formalin-fixed cadavers were included in the cadaver feasibility study. Objective: The aim was to ascertain the anatomical feasibility of extradural contralateral C7 ventral root transfer technique by cervical posterior. Summary of Background Data: Upper limb spastic hemiplegia is a common sequela after stroke. In our previous study, the authors established a method by transferring contralateral C7 dorsal and ventral roots to the corresponding C7 dorsal and ventral roots on the affected side in the cervical posterior. Methods: In the present study, six formalin-fixed cadavers were dissected to confirm the anatomical feasibility. Experimental anastomosis in cadavers was conducted. The pertinent lengths of the extradural nerve roots were measured. The tissue structures surrounding regions between the extradural CC7 nerve roots and the vertebral artery were observed. The cervical magnetic resonance imaging scans of 60 adults were used to measure the distance between the donor and recipient nerves. Results: Experimental anastomosis showed that the distance between the donor and recipient nerves was approximately 1 cm; the short segment of the sural nerve needed bridging. The distance between both exit sites of the exit of the extradural dura mater was 33.57±1.55 mm. The length of the extradural CC7 ventral root was 22.00±0.98 mm. The ventral distance (vd) and the dorsal distance (dd) in males were 23.98±1.72 mm and 30.85±2.22 mm ( P <0.05), while those in females were 23.28±1.51 mm and 30.03±2.16 mm, respectively. C7 vertebral transverse process, ligaments, and other soft tissues were observed between the vertebral artery and the extradural C7 nerve root. Conclusion: Under the premise of less trauma, our study shows that the extradural contralateral C7 ventral root transfer technique, in theory, yields better surgical results, including better recovery of motor function and complete preservation of sensory function. Level of Evidence: 5